(3OZd GdYjfs - (3jhMfG Hf eGShjg, CHh RcQjG,J (B243 (3g` s
(3ChdgG (B:s
(3aj eGgjI GdYjf hcjajJgG hJQcjHgG hYOO QWhHJgG hLejY GdCOhGA GdYGQVI dcd hGMO efgG hYdGL Pdc s
(3BNQgG (B:s
(3TjGa CUaQ JCNP fMGS eMQb hRf YTQI OQGge UeZ YQHi hCajhf , ef cd hGMO hRf OQge , jYed ceG bHdg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B25 - (3U(B75s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B263s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B92 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs